Competing interparticle interactions and surface anisotropy in NiO nanoparticles - Meneses, C. T. (2010)
We report unconventional magnetic properties on NiO nanoparticles of an average diameter of 5.8(7) nm obtained by coprecipitation method. To investigated the effect of the intra and interparticle interactions in the magnetic properties were dispersed in a polyvinyl-pyrrodone matrix at two different concentration. X-ray, ac, and dc magnetization and ferromagnetic resonance experiments were carried out on powder and dispersed NiO systems. Our results show that dispersed and concentrated samples exhibit following two different magnetic behaviors: (i) a high temperature peak related to the blocking of the particle core and (ii) a low temperature maximum likely related to the freezing of the frustrated spins on the surface particle. Besides, we have observed that the low temperature maximum is not field-dependent and dependent strongly on the distance among particles. This result can be understood taking account the decreasing of the dipolar interaction to more dispersed samples.